Advocacy-orientated, advocacy-related and scholarly literature on the Rwandan genocide of 1994 : assessing whether the main points of concern, criticism or dispute about the literature arise from the basic facts and empirical evidence presented or from the interpretive frameworks employed to analyse them - Motlafi, Nompumelelo (Department of Political Studies, 2015)
Includes bibliographical references (leaves 107-114).